Polymorphic Forms of Lamivudine: Characterization, Estimation of Transition Temperature, and Stability Studies by Thermodynamic and Spectroscopic Studies. (14th November 2012) - Chadha, Renu; Arora, Poonam; Bhandari, Swati
Abstract : The present study is focused on estimation of transition temperature and stability of various forms of lamivudine. The forms were recrystallized from variety of solvents and preliminarily identification on the basis of SEM revealed existence of three forms (Forms I, II, III). DSC scans of Forms I and III show that these are metastable and undergo heat mediated transformation to Form IH and Form IIIH, respectively. Form II is phase pure with single sharp melting endotherm at 178.6°C. The thermal events are visually observed by hot stage microscopy. Enthalpy of solution of the forms is endothermic and magnitude varies in the order Form II > Form IL > Form IIIL suggesting Form IIIL to be least crystalline which is well correlated with XRPD data. The transition temperature of the polymorphic pairs IL /IH and IIIL /IIIH derived from enthalpy of solution and solubility data revealed monotropy whereas enantiotropy exists in IIIH /II. The slurry experiments showed Form II to be thermodynamically most stable. Forms IL and IIIL though stable in water are converted to Form II in ethanol, acetonitrile, and propanol after 1 day. Form IIIL is converted to Form IL in water after 7 days and the observation is of importance as this instability can effect the pharmaceutical preparations whereas Form IL shows a balance between stability and solubility.